2019
DOI: 10.1021/acsaem.9b01617
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Nitrogen Reserve and Electronic Regulation in Bamboo-like Carbon Tubules by Cobalt Nanoparticles for Highly Efficient ORR

Abstract: N-doped carbon materials are the promising oxygen reduction reaction (ORR) electrocatalyst for many energy systems such as fuel cells and metal−air batteries. Here we report a facile method to regulate electronic structures of bamboo-like carbon tubules dually by rich N-doping and Co particles decoration via pyrolysis of HNO 3 -treated melamine with Co(OH) 2 nanoparticles in an Ar environment (Co-NC-T). XRD, XAFS, and Raman spectra indicate the abundant decoration of metal Co rather than CoO x , and XPS spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 46 publications
(80 reference statements)
1
20
0
Order By: Relevance
“…X‐ray photoelectron spectrometer (XPS) was used to analyze the element composition and chemical state in N‐CNTs@Co. As shown in Figure 2B, the Co 2p spectrum was fitted with four peaks, and 794.6 and 778.2 eV were related to Co 2p 1/2 and Co 2p 3/2 , respectively, [ 16 ] suggesting that there was zero‐valent cobalt in N‐CNTs@Co. [ 17 ] In addition, there were two characteristic satellite peaks at 804.6 and 780.1 eV. The N spectrum was divided into three characteristic peaks, and the peak at 397.6 eV was attributed to CoN x and the other peaks located at 397.8, 400.5, and 402.1 eV corresponding to pyridinic N, pyrrolic N, and graphitic N, respectively (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…X‐ray photoelectron spectrometer (XPS) was used to analyze the element composition and chemical state in N‐CNTs@Co. As shown in Figure 2B, the Co 2p spectrum was fitted with four peaks, and 794.6 and 778.2 eV were related to Co 2p 1/2 and Co 2p 3/2 , respectively, [ 16 ] suggesting that there was zero‐valent cobalt in N‐CNTs@Co. [ 17 ] In addition, there were two characteristic satellite peaks at 804.6 and 780.1 eV. The N spectrum was divided into three characteristic peaks, and the peak at 397.6 eV was attributed to CoN x and the other peaks located at 397.8, 400.5, and 402.1 eV corresponding to pyridinic N, pyrrolic N, and graphitic N, respectively (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…The diffraction peaks located at 17.3°, 24.7°, 35.1°, 39.6°, 49.7°, 52.7°, 56.1°, and 68.0° were attributed to (200), ( 220), (400), (420), ( 440), (600), (620), and (640) planes of CoHCF. [15] As for N-CNTs@Co, the diffraction peaks located at 25.0° corresponded to the (002) plane of graphitic carbon, and 44.7° was matched with (111) plane of Co. X-ray photoelectron spectrometer (XPS) was used to analyze the element composition and chemical state in N-CNTs@Co. As shown in Figure 2B, the Co 2p spectrum was fitted with four peaks, and 794.6 and 778.2 eV were related to Co 2p 1/2 and Co 2p 3/2 , respectively, [16] suggesting that there was zero-valent cobalt in N-CNTs@Co. [17] In addition, there were two characteristic satellite peaks at 804.6 and 780.1 eV. The N spectrum was divided into three characteristic peaks, and the peak at 397.6 eV was attributed to CoN x and the other peaks located at 397.8, 400.5, and 402.1 eV corresponding to pyridinic N, pyrrolic N, and graphitic N, respectively (Figure 2C).…”
Section: Characterization Of N-cnts@comentioning
confidence: 98%
“… 22 Co-NC bamboolike carbon tubules (HP-Co-CNs) with core Co nanoparticles surrounded by ordered carbon layers showed superior ORR activities, excellent durability, and resistance to methanol in an alkaline medium. 23 Co-N-C nanofibers embedded with Co nanoparticles were prepared for oxygen reduction with high activity and remarkable durability. 24 Although these papers 22 24 have reported that transition metal nanoparticles encapsulated in ordered carbon layers/graphitic carbon/graphene can improve the stability of the catalyst, fewer reports investigated on the growth process and mechanism of transition metal-catalyzed graphitization during the pyrolysis and carbonization process.…”
Section: Introductionmentioning
confidence: 99%
“…The Co/CoO x @Co/N-graphene hybrid electrocatalyst, where the encapsulated Co/CoO x nanoparticles embed in Co/N-doped mesoporous graphene, demonstrated excellent ORR activity, outstanding long-term durability, and resistance to methanol poisoning . Co-NC bamboolike carbon tubules (HP-Co-CNs) with core Co nanoparticles surrounded by ordered carbon layers showed superior ORR activities, excellent durability, and resistance to methanol in an alkaline medium . Co-N-C nanofibers embedded with Co nanoparticles were prepared for oxygen reduction with high activity and remarkable durability .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation